Kinetic Study Of Acetic Acid Production From Banana Stem Waste Using Wild Strain Bacillus Thuringiensis Bmb171 - N., Zainol; Mohd Faizan, Jamaluddin; Aizawati, Abd. Rahman (Global Science Publications, 2014)
The banana stem was abundantly left degraded in the agricultural soilreported to be good substrate for acetic acid production. In this study, the kinetic study of acetic acid production from banana stem waste was conducted using wild strain obtained from soil. Wild strain of Bacillus thuringiensis BMB 171 was found able to produce high amount of acetic acid (1.1 g/l acetic acid from 1.0 g/ l banana stem waste).There is limited study on acetic acid production from banana stem waste using Bacillus thuringiensis BMB 171. The behaviour of the process was studied by fitting the data into suitable kinetic model from literature review at initial concentrations of biomass (SVSS), glucose (SVDS) and acetic acid (STAA) at: (SVSS)0 = 0.0002 g/l; (SVDS)0 = 2.46 g/l; (STAA)0 = 0 g/l.The model was evaluated based on sum squared error between experimental data and theoretical data. The values of calculated kinetic parameters were as followed: k1 = 0.5004 h-1; k2 = 0.0576g /l h; k3 = 0.6197g /l; k4= 0.1294g /l h; k5= 0.9289g / l; k6= 0.0545g /l h; k7= 0.0001g /l. The R2 values obtained from kinetic study were above 0.8. In conclusion, the proposed kinetic model can be used to describe the process.